Sulfation of fulvestrant by human liver cytosols and recombinant SULT1A1 and SULT1E1 - Edavana VK; Yu X; Dhakal IB; Williams S; Ning B; Cook IT; Caldwell D; Falany CN; Kadlubar S (Dove Medical Press, 2011)
Vineetha Koroth Edavana1, Xinfeng Yu1, Ishwori B Dhakal1, Suzanne Williams1, Baitang Ning2, Ian T Cook3, David Caldwell1, Charles N Falany3, Susan Kadlubar11Division of Medical Genetics, College of Medicine, University of Arkansas for Medical Sciences, Little Rock, AR, USA; 2Division of Personalized Nutrition and Medicine, National Center for Toxicological Research, Food and Drug Administration, Jefferson, AR, USA; 3Department of Pharmacology, University of Alabama, Birmingham, AL, USAAbstract: Fulvestrant (Faslodex™) is a pure antiestrogen that is approved to treat hormone receptor-positive metastatic breast cancer in postmenopausal women. Previous studies have demonstrated that fulvestrant metabolism in humans involves cytochromes P450 and UDP-glucuronosyltransferases (UGTs). To date, fulvestrant sulfation has not been characterized. This study examined fulvestrant sulfation with nine recombinant sulfotransferases and found that only SULT1A1 and SULT1E1 displayed catalytic activity toward this substrate, with Km of 4.2 ± 0.99 and 0.2 ± 0.16 µM, respectively. In vitro assays of 104 human liver cytosols revealed marked individual variability that was highly correlated with β-naphthol sulfation (SULT1A1 diagnostic substrate; r = 0.98, P < 0.0001), but not with 17ß-estradiol sulfation (SULT1E1 diagnostic substrate; r = 0.16, P = 0.10). Fulvestrant sulfation was correlated with both SULT1A1*1/2 genotype (P value = 0.023) and copy number (P < 0.0001). These studies suggest that factors influencing SULT1A1/1E1 tissue expression and/or enzymatic activity could influence the efficacy of fulvestrant therapy.Keywords: fulvestrant, sulfotransferase, genotype, copy number